Boron-doped silicon carbon negative electrode material and preparation method and application thereof
Through the preparation of boron doping and porous carbon composite materials on the silicon negative material, the performance problems caused by the volume change in the charging and discharge process of silicon negative pole materials have been solved, and the high magnification performance and good cycle stability are achieved.
Patent Information
- Application Number
- CN202411419452.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The volume of the silicon negative electrode material changes greatly during the charge and discharge process, resulting in the crushing of the electrode material, the formation of solid-electrolyte interface and the consumption of electrolyte, thereby reducing cycle life and performance.
The boron -doped silicon carbon negative material is used to cover the surface of the silicon particles in situ and attach pore making agent on its surface to mix granules and high -temperature pores to form porous carbon composite materials. Carbon covering technology, eventually obtained boron -doped silicon carbon negative materials.
It improves the electronic conductivity of the material and the ionic conductivity, significantly improves the magnification performance, and effectively alleviates the expansion of the silicon negative material, and improves the cycle performance and stability.
Smart Images

Figure CN119381428A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a boron-doped silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion battery is a secondary battery, i.e. a rechargeable battery. It mainly relies on the reciprocating movement of lithium ions between the positive electrode and the negative electrode to work. During the charging and discharging process, Li+ is embedded and de-embedded between the two electrodes: + The lithium ion battery is released from the positive electrode and embedded in the negative electrode through the electrolyte, making the negative electrode in a lithium-rich state; the opposite is true during discharge. Lithium-ion batteries have become the most commonly used energy storage device due to their good environmental compatibility, long cycle life, and low self-discharge rate. They are widely used in portable devices and electric vehicles.
[0003] Among them, Si-based materials have the highest theoretical specific capacity among the materials studied so far, and the alloys formed by them are Li x Si, x ranges from 0 to 4.4, and the theoretical specific capacity of pure silicon is 4200mAh / g. The voltage platform of silicon is slightly higher than that of graphite, and it is difficult to cause surface lithium precipitation during charging, and its safety performance is superior to that of graphite electrodes. In addition, silicon is one of the most abundant elements in the earth's crust, with a wide source and low price. Moreover, silicon alloys do not have a solvation effect like graphite, low lithium insertion potential, low atomic weight, high energy density and high Li mole fraction in Li-Si alloys, and have higher stability than other metals and materials, which has attracted much attention. Therefore, silicon is considered to be the most likely negative electrode material to replace graphite in the short term. Therefore, the development of silicon-based negative electrodes is very attractive.
[0004] However, silicon negative electrode materials have been slow to achieve large-scale commercial applications. While having many advantages, silicon anode materials also have several disadvantages. First, silicon anode materials will experience a volume change of more than 300% during the charging and discharging process. Such a high volume expansion and contraction can easily cause the electrode material to shatter and lose contact with the current collector and the electrode conductive network. At the same time, the volume change brings about the generation of new surfaces, and a new solid-electrolyte interface (SEI) needs to be formed, which leads to a large consumption of electrolyte, and then leads to a significant reduction in cycle life. On the other hand, the electrical conductivity and lithium ion diffusion rate of silicon are lower than those of graphite, which will limit the performance of silicon under high current and high power conditions. Summary of the invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a boron-doped silicon-carbon negative electrode material and a preparation method and application thereof.
[0006] The present invention provides a method for preparing a boron-doped silicon-carbon negative electrode material, comprising the following steps:
[0007] S1, performing borane deposition on the surface of the silicon source to obtain boron-coated silicon particles;
[0008] S2, mixing the boron-coated silicon particles with a pore-forming agent to obtain a mixture A;
[0009] S3, mixing and granulating the mixture A, the carbon source, the carbon nanotubes and the asphalt, and crushing and classifying the granulated product to obtain a mixture B;
[0010] S4, forming pores in the mixture B to obtain a porous carbon composite material;
[0011] S5, subjecting the porous carbon composite material to a vapor phase co-deposition treatment to obtain a mixture C;
[0012] S6. Carbon-coating the mixture C to obtain a boron-doped silicon-carbon negative electrode material.
[0013] The present invention is to coat the surface of silicon particles with boron in situ, then attach a layer of pore-forming agent to the surface, mix and granulate the obtained composite particles with porous carbon sources, carbon nanotubes and asphalt, and then subject the granulated particles to high-temperature pore-forming to obtain a porous carbon material containing boron-coated nano silicon particles, and use a deposition device to co-deposit silane and borane on the obtained porous carbon material, and finally coat the surface of the composite material with a carbon layer to finally obtain a boron-doped silicon-carbon negative electrode material. The material can effectively improve the electronic conductivity and ionic conductivity of the material, can greatly improve the rate performance of the material, and has a good solution effect on the expansion problem of silicon negative electrode materials.
[0014] Preferably, in the S1, the silicon source is selected from one or more of silicon, silicon oxide, silicon monoxide, and lithium silicate.
[0015] Preferably, in the S1, the average particle size of the silicon source is 50 to 200 nm.
[0016] The average particle size of the silicon source within a certain range helps to alleviate the cycling problems caused by the expansion of the negative electrode material.
[0017] Preferably, in the S1, the mass fraction of boron element in the boron-coated silicon particles is 2wt% to 15w%.
[0018] Preferably, in S1, the deposition includes the following conditions: the gas flow rate of borane is 300-600 sccm, the deposition temperature is 550-700° C., and the deposition time is 3-5 hours.
[0019] Preferably, in S2, the pore-forming agent is selected from one or more of zinc chloride, potassium hydroxide, phosphoric acid and potassium carbonate.
[0020] Selecting the type of pore former helps control the reaction rate with the base carbon, and also controls the pore size produced by activation. By adding the pore former to the particles in advance, a more uniform pore structure can be formed inside and outside the particles, which can more effectively alleviate the expansion of silicon.
[0021] Preferably, in the S2, the mass ratio of the boron-coated silicon particles to the pore-forming agent is (70-95): (5-30).
[0022] Preferably, in S3, the mass ratio of mixture A, carbon source, carbon nanotubes and asphalt is 2:(5-7):(0.5-2):(0.5-1).
[0023] Controlling the mass ratio of mixture A, carbon source, carbon nanotubes, and asphalt within a certain range helps to ensure the material capacity efficiency and conductivity.
[0024] Preferably, in S3, the carbon source is selected from one or more of petroleum coke, phenolic resin and coconut shell powder.
[0025] Selecting the type of carbon source helps to improve the strength of the carbon material substrate and can effectively buffer the expansion of the silicon material.
[0026] Preferably, in S3, the average particle size of the carbon source is 1 μm to 10 μm.
[0027] Preferably, in S3, the carbon nanotubes are selected from one or more of linear carbon nanotubes and helical carbon nanotubes.
[0028] Preferably, in S3, the carbon nanotubes have a length of 50 to 500 nm and a diameter of 2 to 10 nm.
[0029] The size of carbon nanotubes within a certain range helps to improve the intrinsic conductivity and ion transport properties of the material, thereby improving the rate performance of the material accordingly.
[0030] Preferably, in S3, the average particle size D50 of the mixture B after crushing and classification is 5-10 μm, and Dmax ≤ 20 μm.
[0031] Preferably, in S3, the granulation method is selected from one or more of melt granulation and sintering granulation.
[0032] Preferably, in the step S3, the granulation temperature is 500-800° C., and the granulation time is 5-10 h.
[0033] Controlling the granulation temperature and time helps to control the particle size and particle strength after granulation.
[0034] Preferably, in S3, a protective gas needs to be introduced during the granulation process, and the protective gas is selected from one of argon, nitrogen, and argon-hydrogen mixed gas.
[0035] Preferably, in said S4, pore formation includes pore formation by chemical activation method and / or pore formation by physical activation method.
[0036] More preferably, the activator for forming pores by chemical activation is selected from one or more of KOH, NaOH, phosphoric acid and zinc chloride.
[0037] Selecting the type of activator for pore formation by chemical activation helps to control the reaction rate with the base carbon, and can also control the pore size produced by activation.
[0038] More preferably, the mass of the activator used for pore formation by chemical activation accounts for 30 wt% to 60 wt% of the mixture B.
[0039] More preferably, the activation temperature of the chemical activation method for pore formation is 800-1200° C., and the activation time is 3 h to 5 h.
[0040] More preferably, the activator for pore formation by physical activation is selected from one or more of water vapor and carbon dioxide gas.
[0041] More preferably, the gas flow rate of the water vapor and carbon dioxide gas is 100-300 sscm.
[0042] More preferably, the activation temperature of the physical activation method for pore formation is 600-1200° C., and the activation time is 5-15 hours.
[0043] Preferably, in S4, the specific surface area of the porous carbon composite material is 1000 to 2000 m 2 / g, pore size is 2~10nm.
[0044] Preferably, in S5, the vapor phase co-deposition treatment includes using silane, borane and hydrogen as reaction gases, the deposition temperature is 400-700° C., and the deposition time is 3-7 hours.
[0045] Controlling the conditions of the vapor phase co-deposition process helps control the amount of silicon and boron deposited in the substrate, thereby controlling the grain size of the silicon and reducing its expansion.
[0046] More preferably, the gas flow ratio of silane, borane and hydrogen is (2-10): (0.2-2): (160-200).
[0047] Preferably, in the above S5, the process further comprises evacuating the furnace chamber to a vacuum pressure of 0.1-5 kPa before the vapor phase co-deposition process.
[0048] Preferably, in S5, the mass of silane and borane is 40wt% to 60wt% of the mixture C.
[0049] Preferably, in said S6, the carbon coating includes liquid phase carbon coating and / or gas phase carbon coating.
[0050] More preferably, the carbon source for the liquid-phase carbon coating is selected from one or more of asphalt, glucose, polyaniline, polypyrrole, polythiophene and polyacrylonitrile.
[0051] More preferably, the carbon source for gas-phase carbon coating is selected from one or more of acetylene, methane, ethane, propane, ethylene and propylene.
[0052] Selecting different types of carbon sources can help reduce the specific surface area of the material and further improve the conductive properties of the material.
[0053] The present invention also provides a boron-doped silicon-carbon negative electrode material prepared by the above preparation method.
[0054] A lithium-ion battery comprises the above-mentioned boron-doped silicon-carbon negative electrode material or the boron-doped silicon-carbon negative electrode material prepared by the above-mentioned preparation method.
[0055] The beneficial effects of the present invention are:
[0056] The present invention deposits borane on the surface of the silicon source, that is, coats the surface with boron, thereby increasing the intrinsic conductivity of the silicon-based negative electrode material, improving the degree of atomic mixing in the silicon-based unit cell, and reducing the expansion rate of the material during the cyclic charge and discharge process; and the coating with boron can effectively isolate the direct contact between the silicon particles and the electrolyte, avoid the generation of side reactions and the consumption of the electrolyte, and improve the cycle performance of the material. The present invention adopts the method of simultaneous internal and external pore formation to make the internal and external distribution of the pore structure in the material more uniform, which can more effectively alleviate the problem of material expansion. The present invention can better improve the conductivity and ion conductivity of the material by adding carbon nanotubes, and improve the rate performance of the material.
[0057] The boron-doped silicon-carbon negative electrode material prepared by the present invention has good cycle performance and rate performance, and the material structure is more stable, thereby achieving the purpose of improving the material battery performance and having good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a schematic diagram of the structure of the boron-doped silicon-carbon negative electrode material proposed in the present invention;
[0059] 1-boron-coated silicon particles, 2-CCNTs, 3-CNTs, 4-surface-coated carbon layer.
[0060] Figure 2This is a comparison chart of the charge and discharge curves of lithium-ion batteries assembled with the negative electrode materials of Example 1 and Comparative Example 1 of the present invention.
[0061] Figure 3 This is the XRD diagram of the boron-doped silicon-carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0062] The technical solution of the present invention is described in detail through specific embodiments.
[0063] Unless otherwise specified, the materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources.
[0064] Example 1
[0065] A method for preparing a boron-doped silicon-carbon negative electrode material comprises the following steps:
[0066] S1. Borane deposition is performed on nano-silicon particles with an average particle size of 50 nm in a CVD furnace. The borane gas flow rate is 300 sccm, the deposition temperature is 600° C., the deposition time is 3 h, and the mass fraction of the deposited boron element is 5 w%, to obtain boron-coated silicon particles;
[0067] S2, mixing the boron-coated silicon particles with the pore-forming agent potassium hydroxide / potassium carbonate in a mass ratio of 3:1 to obtain a mixture A, wherein the mass ratio of potassium hydroxide to potassium carbonate is 3:1;
[0068] S3, mixing and granulating the mixture A, petroleum coke, CCNTs / CNT, and asphalt in a mass ratio of 2:5:1:0.5, at a granulation temperature of 800°C, and crushing and classifying the granulated product to obtain a mixture B with an average particle size of D50 to 7 μm and Dmax to 18 μm; wherein the mass ratio of CCNTs to CNT is 3:2;
[0069] S4. Mixture B was chemically activated to form pores by adding 40 wt% of KOH / NaOH mixture (KOH / NaOH=3:1), and activated at 900°C for 3 h. The excess activator was removed by using 0.5 mol / L hydrochloric acid solution, and then washed with water to remove the excess acid solution, and centrifuged and dried to obtain a specific surface area of 1800 m 2 / g, porous carbon composite material with a pore size of 2nm;
[0070] S5, transferring the porous carbon composite material to a PECVD furnace, evacuating the furnace chamber to 0.1 kPa, and during the deposition process, controlling the gas flow rate of silane to 6 sccm, the gas flow rate of borane to 1 sccm, the gas flow rate of hydrogen to 180 sccm, the deposition temperature to 550°C, and the deposition time to 5.5 h to obtain a mixture C;
[0071] S6. Carry out vapor phase carbon coating on the mixture C to obtain a boron-doped silicon-carbon negative electrode material.
[0072] Example 2
[0073] A method for preparing a boron-doped silicon-carbon negative electrode material comprises the following steps:
[0074] S1. Borane deposition is performed on nano-silicon particles with an average particle size of 50 nm in a CVD furnace. The borane gas flow rate is 300 sccm, the deposition temperature is 500° C., the deposition time is 2 h, and the mass fraction of the deposited boron element is 5 w%, to obtain boron-coated silicon particles;
[0075] S2, mixing the boron-coated silicon particles with the pore-forming agent potassium hydroxide / potassium carbonate in a mass ratio of 3:1 to obtain a mixture A, wherein the mass ratio of potassium hydroxide to potassium carbonate is 3:1;
[0076] S3, mixing and granulating the mixture A, petroleum coke, CCNTs / CNT, and asphalt in a mass ratio of 2:5:1:0.5, at a granulation temperature of 800°C, and crushing and classifying the granulated product to obtain a mixture B with an average particle size of D50-7 μm and Dmax-18 μm, wherein the mass ratio of CCNTs to CNT is 3:1;
[0077] S4. Mixture B was chemically activated to form pores by adding 40 wt% of KOH / NaOH mixture (KOH / NaOH=3:1), and activated at 900°C for 3 h. The excess activator was removed by using 0.5 mol / L hydrochloric acid solution, and then washed with water to remove the excess acid solution, and centrifuged and dried to obtain a specific surface area of 1800 m 2 / g, porous carbon composite material with a pore size of 2nm;
[0078] S5, transferring the porous carbon composite material to a PECVD furnace, evacuating the furnace chamber to 0.1 kPa, and during the deposition process, controlling the gas flow rate of silane to 6 sccm, the gas flow rate of borane to 1 sccm, the gas flow rate of hydrogen to 180 sccm, the deposition temperature to 550°C, and the deposition time to 5.5 h to obtain a mixture C;
[0079] S6. Carry out vapor phase carbon coating on the mixture C to obtain a boron-doped silicon-carbon negative electrode material.
[0080] Example 3
[0081] A method for preparing a boron-doped silicon-carbon negative electrode material comprises the following steps:
[0082] S1. Borane deposition is performed on nano-silicon particles with an average particle size of 50 nm in a CVD furnace. The borane gas flow rate is 300 sccm, the deposition temperature is 500° C., the deposition time is 2 h, and the mass fraction of the deposited boron element is 5 w%, to obtain boron-coated silicon particles;
[0083] S2, mixing the boron-coated silicon particles with the pore-forming agent potassium hydroxide / potassium carbonate in a mass ratio of 3:1 to obtain a mixture A, wherein the mass ratio of potassium hydroxide to potassium carbonate is 3:1;
[0084] S3, mixing and granulating the mixture A, petroleum coke, CCNTs / CNT, and asphalt in a mass ratio of 2:5:1:0.5, at a granulation temperature of 800°C, and crushing and classifying the granulated product to obtain a mixture B with an average particle size of D50 to 5 μm and Dmax to 12 μm, wherein the mass ratio of CCNTs to CNT is 3:2;
[0085] S4. Mixture B was chemically activated to form pores by adding 40 wt% of KOH / NaOH mixture (KOH / NaOH=3:1), and activated at 900°C for 3 h. The excess activator was removed by using 0.5 mol / L hydrochloric acid solution, and then washed with water to remove the excess acid solution, and centrifuged and dried to obtain a specific surface area of 1800 m 2 / g, porous carbon composite material with a pore size of 1.5nm;
[0086] S5, transferring the porous carbon composite material to a PECVD furnace, evacuating the furnace chamber to 0.1 kPa, and during the deposition process, controlling the gas flow rate of silane to 6 sccm, the gas flow rate of borane to 1 sccm, the gas flow rate of hydrogen to 180 sccm, the deposition temperature to 550°C, and the deposition time to 5.5 h to obtain a mixture C;
[0087] S6. Carry out vapor phase carbon coating on the mixture C to obtain a boron-doped silicon-carbon negative electrode material.
[0088] Comparative Example 1
[0089] The GROUP14 silicon-carbon negative electrode material sold on the market is used as the negative electrode material.
[0090] Comparative Example 2
[0091] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0092] S1. Borane deposition is performed on nano-silicon particles with an average particle size of 50 nm in a CVD furnace. The borane gas flow rate is 500 sccm, the deposition temperature is 600° C., the deposition time is 5 h, and the mass fraction of the deposited boron element is 10 w%, to obtain boron-coated silicon particles;
[0093] S2, mixing the boron-coated silicon particles with the pore-forming agent potassium hydroxide / potassium carbonate in a mass ratio of 3:1 to obtain a mixture A, wherein the mass ratio of potassium hydroxide to potassium carbonate is 3:5;
[0094] S3, mixing mixture A, petroleum coke and asphalt in a mass ratio of 2:5:1 for granulation at a granulation temperature of 800°C, crushing and classifying the granulated product to obtain mixture B with D50~7μm and Dmax~18μm;
[0095] S4. Mixture B was chemically activated to form pores by adding 40 wt% of KOH / NaOH mixture (KOH / NaOH=3:1), and activated at 900°C for 3 h. The excess activator was removed by using 0.5 mol / L hydrochloric acid solution, and then washed with water to remove the excess acid solution, and centrifuged and dried to obtain a specific surface area of 1800 m 2 / g, porous carbon composite material with a pore size of 1.5nm;
[0096] S5, transferring the porous carbon composite material to a PECVD furnace, evacuating the furnace chamber to 0.1 kPa, and during the deposition process, controlling the gas flow rate of silane to 6 sccm, the gas flow rate of borane to 1 sccm, the gas flow rate of hydrogen to 180 sccm, the deposition temperature to 550°C, and the deposition time to 5.5 h to obtain a mixture C;
[0097] S6. Carry out gas-phase carbon coating on the mixture C to obtain a silicon-carbon negative electrode material.
[0098] Comparative Example 3
[0099] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0100] S1. Mix nano silicon particles with an average particle size of 50 nm and pore-forming agent potassium hydroxide / potassium carbonate in a mass ratio of 3:1 to obtain a mixture A, wherein the mass ratio of potassium hydroxide to potassium carbonate is 3:5;
[0101] S3, mixing and granulating the mixture A, petroleum coke, CCNTs / CNT, and asphalt in a mass ratio of 2:5:1:0.5, at a granulation temperature of 800°C, crushing and classifying the granulated product to obtain a mixture B with an average particle size of D50 to 7 μm and Dmax to 18 μm; wherein the mass ratio of CCNTs to CNT is 3:1;
[0102] S4. Mixture B was chemically activated to form pores by adding 40 wt% of KOH / NaOH mixture (KOH / NaOH=3:1), and activated at 900°C for 3 h. The excess activator was removed by using 0.5 mol / L hydrochloric acid solution, and then washed with water to remove the excess acid solution, and centrifuged and dried to obtain a specific surface area of 1500 m 2 / g, porous carbon composite material with a pore size of 2nm;
[0103] S5, transferring the porous carbon composite material to a PECVD furnace, evacuating the furnace chamber to 0.1 kPa, and during the deposition process, controlling the gas flow rate of silane to 6 sccm, the gas flow rate of hydrogen to 180 sccm, the deposition temperature to 550°C, and the deposition time to 5.5 h to obtain a mixture C;
[0104] S6. Carry out gas-phase carbon coating on the mixture C to obtain a silicon-carbon negative electrode material.
[0105] The above silicon-carbon negative electrode material is mixed with graphite with a gram capacity of 600 mAh / g, and then slurried with sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and conductive carbon black (SP) in a mass ratio of 94:3:2:1. After coating, rolling, slitting and other processes, the negative electrode sheet is prepared and assembled with the positive electrode sheet, electrolyte, and separator into a lithium-ion battery.
[0106] The lithium ion batteries of the silicon-carbon negative electrode materials of Examples 1 to 3 and Comparative Examples 1 to 3 were tested for their expansion rate and rate performance during the cyclic charge and discharge process. The test results are shown in Table 1.
[0107] Table 1
[0108] serial number Full electrode expansion rate Double charge capacity retention rate (3C) Discharge capacity retention rate (3C) Example 1 40% 88% 92% Comparative Example 1 55% 80% 85% Comparative Example 2 45% 82% 88% Comparative Example 3 45% 85% 90%
[0109] It can be seen from the data in Table 1 that the boron-doped silicon-carbon negative electrode material prepared by the present invention has a smaller expansion rate and better rate performance. It can be seen from Comparative Example 1 and Example 1 that the commercially available silicon-carbon negative electrode material has a larger full-charge expansion rate than Example 1 of the present invention, and the negative electrode material of the present invention has excellent rate performance; it can be seen from the data of Comparative Example 2, Comparative Example 3 and Example 1 that the negative electrode material without adding CCNTs / CNTs or boron coating has a weaker comprehensive rate performance than the negative electrode material of the embodiment of the present invention.
[0110] like Figure 1 As shown, Figure 1 This is a schematic diagram of the structure of the boron-doped silicon-carbon negative electrode material proposed in the present invention. Figure 2 This is a comparison chart of the charge and discharge curves of lithium-ion batteries assembled with the negative electrode materials of Example 1 of the present invention and Comparative Example 1. Figure 2It can be seen that since the base carbon material used in the present invention adopts a process of simultaneously making pores inside and outside, the silicon deposition amount is larger and more uniform, so the capacity and first effect of the material are higher than those of comparative example 1. Figure 3 This is the XRD pattern of the boron-doped silicon-carbon negative electrode material prepared in Example 1 of the present invention. Figure 3 It can be seen that due to the large amount of silicon deposition in the embodiment, the silicon peak of the material is relatively high. At the same time, due to the existence of the internal porous structure, an internal buffer space is provided for the material, so the cycle performance of the material will be improved.
[0111] In summary, the boron-doped silicon-carbon negative electrode material provided by the present invention has good cycle performance and rate performance.
[0112] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a boron-doped silicon-carbon negative electrode material, characterized in that: The following steps are involved: S1, performing borane deposition on the surface of the silicon source to obtain boron-coated silicon particles; S2, mixing the boron-coated silicon particles with a pore-forming agent to obtain a mixture A; S3, mixing and granulating the mixture A, the carbon source, the carbon nanotubes and the asphalt, and crushing and classifying the granulated product to obtain a mixture B; S4, forming pores in the mixture B to obtain a porous carbon composite material; S5, subjecting the porous carbon composite material to a vapor phase co-deposition treatment to obtain a mixture C; S6. Carbon-coating the mixture C to obtain a boron-doped silicon-carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: In the S1, the average particle size of the silicon source is 50 to 200 nm.
3. The preparation method according to claim 1, characterized in that: In the S2, the pore-forming agent is selected from one or more of zinc chloride, potassium hydroxide, phosphoric acid, and potassium carbonate.
4. The preparation method according to claim 1, characterized in that: In the S3, the mass ratio of mixture A, carbon source, carbon nanotubes and asphalt is 2:(5-7):(0.5-2):(0.5-1); the carbon source is selected from one or more of petroleum coke, phenolic resin and coconut shell powder.
5. The preparation method according to claim 1, characterized in that: In the step S3, the granulation temperature is 500-800° C. and the granulation time is 5-10 hours.
6. The preparation method according to claim 1, characterized in that: In the above-mentioned S4, pore formation includes chemical activation pore formation and / or physical activation pore formation; the activator of the chemical activation pore formation is selected from one or more of KOH, NaOH, phosphoric acid, and zinc chloride.
7. The preparation method according to claim 1, characterized in that: In the above-mentioned S5, the vapor phase co-deposition treatment includes using silane, borane and hydrogen as reaction gases, the deposition temperature is 400-700° C., and the deposition time is 3-7 hours.
8. The preparation method according to claim 1, characterized in that: In the above-mentioned S6, the carbon coating includes liquid phase carbon coating and / or gas phase carbon coating.
9. A boron-doped silicon-carbon negative electrode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The invention comprises the boron-doped silicon-carbon negative electrode material as claimed in claim 9 or the boron-doped silicon-carbon negative electrode material prepared by the preparation method as claimed in any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of boron nitride-coated carbon nanotubes
CN103172050A
Silicon-based negative electrode material and preparation method thereof
CN113725409A
Boron-doped silicon carbon negative electrode material, preparation method thereof and lithium ion battery
CN117613225A
Carbon-silicon negative electrode material, preparation method thereof and lithium ion battery
CN118712355A
Negative electrode material for nonaqueous electrolyte secondary battery and method for producing the same, lithium ion secondary battery, and electrochemical capacitor
JP2012099341A